Pembelajaran Dalam Talian: Strategi Daya Tindak Terhadap Tekanan Akademik Semasa Norma Baharu - Abdul Rashid Abdul Aziz; Mohd Khairul Anuar Rahimi; Amin Al Haadi Shafie; Rezki Perdani Sawai; Umi Hamidaton Mohd Soffian Lee; Siti Nubailah Mohd Yusof (USIM Press, 2024)
Vol. 6 No. 2 (2021): Jurnal Sains Insani